Eco-friendly polysaccharide coatings for antifouling and drag-reduction and potential application for marine devices - Hao Yang; Liguo Qin; Wenhui Zhao; Fagla Jules Mawignon; Hui Guo; Yongkang Wu; Yali Zhang; Guangneng Dong (Friction)
Abstract Traditional antifouling agents usually have a certain toxic effect on marine environments and non-target organisms. In this study, Dictyophora indusiata polysaccharide (DIP) was applied as a natural antifouling surface modifier to prepare the surface coating for marine antifouling. Three DIP coatings were prepared: D. indusiata spore polysaccharide (DISP), D. indusiata volva polysaccharide (DIVP), and D. indusiata embryonic body polysaccharide (DIEP). The antifouling, tribological, and anticorrosion behavior of the coatings were examined. Results revealed that the three kinds of DIP coatings had excellent antifouling properties, which could effectively prevent the adhesion of Chlorella and the attachment of water-based and oily stains on the surface. Additionally, the coatings showed great mechanical stability and could maintain an extremely low coefficient of friction (COF < 0.05) after continuous wear. The drag reduction rate of the coated surfaces reached 5%, showing a powerful lubrication performance. Furthermore, the DIP coatings presented an outstanding corrosion resistance, where the equivalent circuit impedances were 4–9 orders of magnitude higher than the control groups. This research showed a promising prospect of surface coating fabrication with DIP for marine devices to achieve the purpose of antifouling and drag reduction.